Capital inflows, exchange rate and agricultural output in Nigeria - Fredrick Ikpesu; Abraham Emmanuel Okpe (Future Business Journal, 2019)
The study applied the autoregressive distributed lag (ARDL) technique in investigating the effect of capital inflows and exchange rate on agricultural output in Nigeria between the periods 1981 and 2016. The technique was selected because the variables are integrated at both 1(1) and 1(0) and the sample size is considerably small. Variables used in the study are agricultural output (AO), private capital inflow (PRCI), public capital inflow (PUBCI), investment (INV), labor (L) and real effective exchange rate. Findings from the empirical research revealed that the variables are cointegrated. The research outcome also indicates that in the short run and long run, private capital inflow and public capital inflow positively affect the country agricultural output. The study also revealed that exchange rate depreciation would cause agricultural output to decline in the short and long run. Based on the research findings, it is recommended that the government should create an enabling and conducive environment to attract more inflows of foreign capital into the country to boost the agricultural output. Also, monetary authority should ensure the stability of the country's exchange rate (Naira) since exchange rate depreciation affects agricultural output negatively. Furthermore, there is the need for the harmonization of foreign capital inflow policy and monetary policy by the government, taking into consideration the optimal level of capital inflow that will not have a detrimental effect on exchange rate so as to ensure sustainable growth in agricultural output.
Keywords: F01; Q01; C03; 650; Capital inflows; Agricultural output; Exchange rate; ARDL; Nigeria